2019
DOI: 10.1370/afm.2421
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Primary Care Practitioner Empathy and Risk of Cardiovascular Events and All-Cause Mortality Among Patients With Type 2 Diabetes: A Population-Based Prospective Cohort Study

Abstract: PURPOSE To examine the association between primary care practitioner (physician and nurse) empathy and incidence of cardiovascular disease (CVD) events and all-cause mortality among patients with type 2 diabetes. METHODS This was a population-based prospective cohort study of 49 general practices in East Anglia (United Kingdom). The study population included 867 individuals with screen-detected type 2 diabetes who were followed up for an average of 10 years until December 31, 2014 in the Anglo-Danish-Dutch Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 51 publications
1
63
0
3
Order By: Relevance
“…[11][12][13] Research also suggests that this relationship increases patient satisfaction and may improve clinical outcomes. [14][15][16] The importance of personal aspects of the doctor-patient relationship featured prominently in these results. Some participants' comparisons of the relationship to friendship and one participant's reference to 'loving' patients reflect previous research.…”
Section: Discussionmentioning
confidence: 81%
“…[11][12][13] Research also suggests that this relationship increases patient satisfaction and may improve clinical outcomes. [14][15][16] The importance of personal aspects of the doctor-patient relationship featured prominently in these results. Some participants' comparisons of the relationship to friendship and one participant's reference to 'loving' patients reflect previous research.…”
Section: Discussionmentioning
confidence: 81%
“…Observational studies report (among other things) that enhanced empathy reduces mortality by 50% among diabetic patients, 3 reduces symptom burden and improves wellbeing, 6 increases patient enablement, 8 increases patient safety, 5 improves self-efficacy and adherence 9 and reduces practitioner burnout. 4 …”
Section: Benefits Of Empathy (Likely To Favourably Influence Cost-effmentioning
confidence: 99%
“… 2 These trials suggest that compared with ‘usual care’, empathic positive communication can reduce pain, improve patient satisfaction and increase quality of life. Observational studies suggest that empathic care has benefits ranging from reducing mortality 3 and practitioner burnout 4 to increasing safety. 5 On the other hand, these very same studies reveal that additional time is required to undertake empathy training and to treat patients in the clinic; both of these can be costly.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that continuity of care, encouraged in general practice and not possible in A&E, is associated with reduced mortality 7 . A study of patients with type-2 diabetes demonstrated that higher levels of empathy from practitioners reduced all-cause mortality 8 . In addition GP empathy has been shown to have psychosocial benefits 9 .…”
Section: Cost Implicationsmentioning
confidence: 99%